Hippocampal subfield volumetry in subjects at high risk of dementia: The PREVENT‐Dementia study: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Dounavi, Maria‐Eleni; Mak, Elijah; Wells, Katie; Ritchie, Karen; Ritchie, Craig W.; Su, Li; O'Brien, John T.
Abstract: Background: It is now well‐established that pathological brain alterations in Alzheimer's disease (AD) patients start occurring decades before symptom onset. The earliest detectable neuroimaging finding during the disease's preclinical stage is amyloid plaque deposition. During the disease's prodromal period, hippocampal atrophy is observed. However, it has been suggested that individual hippocampal subfields might demonstrate atrophy at an earlier stage. Our goal in the present study was to investigate the volume of individual hippocampal subfields along with their rate of volumetric change in cognitively normal middle‐aged subjects at high risk of AD using multi‐modal MRI. Method: PREVENT‐Dementia study participants were recruited based on their dementia family history (FH). The participants' age ranged between 40 and 59 years old and they were scanned at two time‐points (visit 1: 183 participants; visit 2: 155 participants). Hippocampal subfields were segmented using Freesurfer and information from a T1‐weighted MPRAGE scan (TR=2.3s /TE=2.98ms, voxel size=1mm 3 ) and a high‐resolution T2 coronal hippocampal acquisition (TR=9s/TE=94ms, voxel size=0.4x0.4x4.0mm 3 ). The volume of the subiculum, CA1, CA2‐3, dentate gyrus & CA4, molecular layer, hippocampal fissure, hippocampal tail and the whole hippocampus were quantified and normalised to total brain volume. The volume of each subfield along with its rate of volumetric change were compared between FH positive and negative subjects and APOE ε4 carriers and non‐carriers using linear regression with age, sex and years of education as covariates. Result: APOE ε4 carriers had a significantly decreased molecular layer volume (figure 1) compared to controls at both study time‐points (visit 1: p < 0.01; visit2: p = 0.02). There were no other differences in the examined subfields, whole hippocampal volume and the rate of volumetric change between the groups. Conclusion: The molecular layer encompasses the stratum radiatum lacunosum and moleculare which is one of the earliest regions to be influenced in AD and has demonstrated high efficiency in separating amyloid positive and negative subjects. Our results suggest that the molecular layer could be amongst the first hippocampal subfields to demonstrate an atrophic pattern in mid‐aged APOE ε4 carriers, in the absence of whole hippocampal, CA1 or subiculum atrophy.